Long-peptide vaccination with driver gene mutations in p53 and Kras induces cancer mutation-specific effector as well as regulatory T cell responses - Quandt, Jasmin; Cid Arregui, Angel; Schölch, Sebastian; Reißfelder, Christoph; Schneider, Martin; Wiemann, Stefan; Momburg, Frank; Beckhove, Philipp (OncoImmunology, 2018)
Mutated proteins arising from somatic mutations in tumors are promising targets for cancer immunotherapy. They represent true tumor-specific antigens (TSAs) as they are exclusively expressed in tumors, reduce the risk of autoimmunity and are more likely to overcome tolerance compared to wild-type (wt) sequences. Hence, we designed a panel of long peptides (LPs, 28-35 aa) comprising driver gene mutations in TP35 and KRAS frequently found in gastrointestinal tumors to test their combined immunotherapeutic potential. We found increased numbers of T cells responsive against respective mutated and wt peptides in colorectal cancer patients that carry the tested mutations in their tumors than patients with other mutations. Further, active immunization of HLA(-A2/DR1)-humanized mice with mixes of the same mutated LPs yielded simultaneous, polyvalent CD8+/CD4+ T cell responses against the majority of peptides. Peptide-specific T cells possessed a multifunctional cytokine profile with CD4+ T cells showing a TH1-like phenotype. Two mutated peptides (Kras[G12V], p53[R248W]) induced significantly higher T cell responses than corresponding wt sequences and comprised HLA-A2/DR1-restricted mutated epitopes. However, vaccination with the same highly immunogenic LPs strongly increased systemic regulatory T cells (Treg) numbers in a syngeneic sarcoma model over-expressing these mutated protein variants and resulted in accelerated tumor outgrowth. In contrast, tumor outgrowth was delayed when vaccination was directed against tumor-intrinsic Kras/Tp53 mutations of lower immunogenicity. Conclusively, we show that LP vaccination targeting multiple mutated TSAs elicits polyvalent, multifunctional, and mutation-specific effector T cells capable of targeting tumors. However, the success of this therapeutic approach can be hampered by vaccination-induced, TSA-specific Tregs.
Gesehen am 18.05.2020